Asymmetric Distribution of Gene Expression in the Centromeric Region of Rice Chromosome 5 - Mizuno, Hiroshi; Kawahara, Yoshihiro; Wu, Jianzhong; Katayose, Yuichi; Kanamori, Hiroyuki; Ikawa, Hiroshi; Itoh, Takeshi; Sasaki, Takuji; Matsumoto, Takashi (Frontiers in Plant Science, 2011)
There is controversy as to whether gene expression is silenced in the functional centromere. The complete genomic sequences of the centromeric regions in higher eukaryotes have not been fully elucidated, because the presence of highly repetitive sequences complicates many aspects of genomic sequencing. We performed resequencing, assembly, and sequence finishing of two P1-derived artificial chromosome clones in the centromeric region of rice (Oryza sativa L.) chromosome 5 (Cen5). The pericentromeric region, where meiotic recombination is silenced, is located at the center of chromosome 5, and is 2.14 Mb in length; a total of six restriction-fragment-length polymorphism markers (R448, C1388, S20487S, E3103S, C53260S, and R2059) genetically mapped at 54.6 cM were located in this region. In the pericentromeric region, 28 genes were annotated on the short arm and 45 genes on the long arm. To quantify all transcripts in this region, we performed massive parallel sequencing of mRNA. Transcriptional density (total length of transcribed region/length of the genomic region) and expression level (number of uniquely mapped reads/length of transcribed region) were calculated on the basis of the mapped reads on the rice genome. Transcriptional density and expression level were significantly lower in Cen5 than in the average of the other chromosomal regions. Moreover, transcriptional density in Cen5 was significantly lower on the short arm than on the long arm; the distribution of transcriptional density was asymmetric. The genomic sequence of Cen5 has been integrated into the most updated reference rice genome sequence constructed by the International Rice Genome Sequencing Project.